Serum level of vitamin D in patients with recurrent aphthous stomatitis: A systematic review and meta‐analysis of case control studies - Roya Safari‐Faramani; Mohsen Salehi; Saman Ghambari Haji Shore; Neda Omidpanah (Wiley, 2024)
Abstract Objectives Recurrent aphthous stomatitis (RAS) is an ulcerative condition with unknown etiology. The effect of vitamin D in the etiology of RAS is still a matter of controversy. In this study, we aimed at review the available evidence on the role of vitamin D deficiency in RAS etiology. Material and Methods PubMed, Cochrane Library for Systematic Reviews, ISI Web of Science, Scopus, and EmBase were systematically searched for evidence on RAS and vitamin D up to January 2020. Retrieved records were screened and assessed by two of the authors independently. Newcastle−Ottawa scale was used to assess the quality of individual studies. AMSTAR tool was used for assessing the quality of the study. Results Eight studies including 383 healthy control and 352 patients with RAS were eligible for the meta‐analysis. Serum vitamin D levels were significantly lower in RAS patients. The weighted mean difference was −7.90 (95% CI: −11.96 to −3.85). Conclusions The results highlighted the importance of vitamin D deficiency in the etiology of RAS. However, more studies are needed to reach a robust decision. The observed association between vitamin D and RAS is probably due to the effect of vitamin D on the immune system.